Covid-19 Pandemic Digitalization Training For Agriculture Sustainable Development of Micro and Small Enterprises In KWT Sri Rejeki - Yeni Pramita; Keppi Sukesi; Reza Safitri (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
It is undeniable that the coronavirus (COVID-19) pandemic has affected the global economy and environment. The main victims of the COVID-19 outbreak are agricultural Micro and Small Enterprises MSEs in KWT, especially in developing countries, where the use of digital media is still limited. This paper uses literature and personal insights to provide lessons on digitalization the COVID-19 pandemic for the development of MSEs in sustainable KWTs from a technology-for-social perspective. researchers develop work concepts to support digital transformation after COVID-19 for the sustainable development of KWT MSEs. The fact is that digital payments, especially mobile money, must be an important digital transformation priority for MSEs in KWT. In addition, institutions must support the resources and capabilities of MSEs in KWT adopting digital for sustainable business, production and consumption. This study shows that the Chair of the KWT UMK and other stakeholders to re-research their business strategy, combine crisis scenarios and business plans as an effort to retain customers virtually so that they can increase sustainable agricultural businesses. We also propose further research areas to enhance the transformation of digital KWT MSEs after COVID-19.